Pengaruh Model Pembelajaran Predict-Observe-Explain terhadap Kecerdasan Logis Matematis Siswa Kelas IV SD - Lisdiana Utami; Cucun Sunaengsih; Regina Lichteria Panjaitan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
This study was motivated by the limited implementation of learning models that specifically develop elementary school students’ logical-mathematical intelligence in science learning. Although the Predict-Observe-Explain (POE) model has been widely used, studies linking it to logical-mathematical intelligence remain limited. This study aims to analyze the implementation and influence of the POE learning model on the logical-mathematical intelligence of fourth-grade students on the topic of changes in states of matter. This study employed a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The research sample consisted of 35 students in the experimental group and 30 students in the control group, determined using a saturated sampling technique. Data were collected through observation, pretest, and posttest and were then analyzed through statistical tests. The results showed that the implementation of POE learning was carried out very well and had a significant effect on improving students’ logical-mathematical intelligence, with a significance value of 0.000 (< 0.05). The improvement score in the experimental class was also higher than that in the control class, namely 0.4577 > 0.2331. These findings affirm that students’ active involvement in the predict, observe, and explain stages contributes to the development of logical-mathematical intelligence. The conclusion of this study indicates that the POE learning model is effective for developing students’ logical-mathematical intelligence in science learning. The implications of this study provide practical contributions for teachers in designing science learning that is more active, meaningful, and oriented toward strengthening elementary school students’ logical-mathematical thinking skills.